National accounts of the Netherlands 2013 (The Hague: Statistics Netherlands, 2014)
The national accounts offer a systematic and consistent overview of the Dutch economy. These official overview statistics play a key role in economic and monetary policy-making and form the basis of the economic predictions and analyses of the Netherlands Bureau for Economic Policy Analysis. The national accounts are also crucial in determining payments to the European Union and in determining the extent to which the Netherlands meets the EMU norm. The economic growth, the budget deficit, and disposable household income are some of the major macro-economic indicators of the national accounts. Furthermore the national accounts provide figures about consumption, investments, imports and exports, and employment.
Macroeconomics -- Supply, Use and input-output tables -- Final expenditure -- Production and generation of income -- Labour -- Sector accounts -- Other tables -- Explanations
Keywords: Netherlands; Finance; National income; National income--Accounting